2001
DOI: 10.1002/app.1884
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of syndiotacticity‐rich ultrahigh molecular weight poly(vinyl alcohol) dilute solution

Abstract: Viscoelastic behavior of the dilute solution of ultrahigh molecular weight syndiotactic poly(vinyl alcohol) (UHMW s-PVA)/dimethyl sulfoxide (DMSO)/water was investigated through rheological response. Below a critical temperature, the dynamic storage modulus (GЈ) of the solution became greater than the dynamic loss modulus (GЉ) and the viscoelastic exponent for GЈ became smaller than that for GЉ before macroscopic gelation, which indicates the evolution of viscoelastic solid properties at the sol state. Also, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…According to Gilsenan and Ross-Murphy (2000), this behavior of G 00 , with a minimum in function of the frequency, could be considered as typical of gelatin based systems, and may be associated with relaxation processes that occur at large time scales. On another hand, in pure PVA solutions, a monotonic increase of G 00 in function of the frequency was observed (Choi et al, 2001).…”
Section: Frequency Sweep Testsmentioning
confidence: 95%
“…According to Gilsenan and Ross-Murphy (2000), this behavior of G 00 , with a minimum in function of the frequency, could be considered as typical of gelatin based systems, and may be associated with relaxation processes that occur at large time scales. On another hand, in pure PVA solutions, a monotonic increase of G 00 in function of the frequency was observed (Choi et al, 2001).…”
Section: Frequency Sweep Testsmentioning
confidence: 95%
“…The mechanical viscoelastic behavior is one of the most important physical properties of polymers, and many studies have been conducted on the viscoelasticity of polymer solids17–19 and polymer solutions 20, 21. However, similar studies on PVAs with high r values have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the low molecular weight PVA solutions (Figure 5), the higher molecular weight PVA solutions exhibit slopes less than 2, as shown in Figure 6. It has been reported that heterogeneous polymer systems such as thermotropic liquidcrystalline polymers in their nematic phase show a decreased slope below 2 in the plot of storage modulus against loss modulus, and give rise to an inflection point in the curve [19][20] .…”
Section: Resultsmentioning
confidence: 99%